Fate of organic solvent-soluble extractives and arabinogalactan during brown rot degradation of siberian larch heartwood - Belt, Tiina; Harju, Anni; Venäläinen, Martti; Kilpeläinen, Petri (Springer Nature, 2024)
The decay resistance of durable heartwoods is primarily due to heartwood extractives, but some extractives have been found to be degradable by wood decaying fungi. We investigated the degradation of heartwood extractives in Siberian larch by the brown rot fungi Coniophora puteana and Rhodonia placenta and found that neither fungus caused the degradation of flavonoids, the primary organic solvent-soluble extractives in the larch samples. However, both fungi caused the gradual depletion of arabinogalactan, the polysaccharide extractive found in larch heartwood.
Keywords: heartwood extractives; decay resistance; brown rot fungi; flavonoids; arabinogalactan